UTILIZING ADDIE MODEL TO DEVELOP SEMESTER INSTURCTIONAL PLAN OF READING COURSE AT ENGLISH EDUCATION DEPARTMENT - Tri Ilma Septiana (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study aims to help the English Education Department at UIN Sultan Maulana Hasanuddin Banten develop its semester instructional plans and reading course materials. The ADDIE Model was utilized in this study's research and development process to create an effective semester instructional plan and to create reading materials. Meantime, a number of tools were employed in this study to collect data, including questionnaires issued to students, interviews, curriculum document analysis for EED, and consult to curriculum experts and literacy practitioners. The finding of this study reveals that lecturers must choose learning objectives that are in accordance with the National Standard for Higher Education when creating semester instructional plans for reading courses. Moreover, in order to help students build some reading abilities and help them become proficient readers, reading strategies and instructional materials at each reading course should be arranged gradually while taking into account students' language development and thinking ability.